Figuring Digital Cascades: Issue Framing in Digital Media Ecosystems - Nathalie Casemajor; Sylvain Rocheleau (Journal of Digital Social Research)
On November 17, 2015, the newly elected Canadian government led by Justin Trudeau made an announcement that became a turning point in the heated debate around the plan to build the Memorial to the Victims of Communism in Ottawa. The government’s decision to scale the project down was massively republished and generated a heavy stream of 2,055 publications and interactions. The virality of such phenomena is sometimes described in the literature as an “information cascade” characterized by a complex and expanding series of media content that is republished, shared, and commented upon in digital public spheres, reaching a growing number of people. Our research aim is twofold. From a theoretical point of view, we combine Entman’s cascade model with the perspective of platform studies. From an empirical point of view, we put this model to the test through a case study of the cascading data flows that emerged during this public debate. We found three key factors that constituted and shaped this information cascade: 1) the economic structure of the Canadian media market, and especially the concentration of media ownership, which is notably high in the Canadian media ecosystem; 2) data-exchange mechanisms and algorithmic filtering that drive the process of news aggregation, quickly spreading media content without being a significant source of user engagement; 3) grassroots engagement in diasporic media, which activates micro public spheres around nested interests and political standpoints regarding the public issue.